Alfabetização em tempos de pandemia da Covid-19: desafios enfrentados por professores, pais e alunos - GUIMARÃES, Allana Caroline da Silva (2022)
This article aims to know the challenges faced by teachers, parents and students of a literacy class at the Escola Municipal de Ensino Infantil e Fundamental Alegria de Saber, during the Covid-19 pandemic. The questions that guided the research were: how did the reading and writing teaching activities take place? What support do parents provide for children to carry out school activities at home? What most compromised children's learning during the pandemic? The research has a qualitative and quantitative nature, and was carried out in two stages: the first stage was carried out with interviews with two teachers from the literacy class and a questionnaire was made available to twelve parents with closed questions about their children's literacy and difficulties faced during the pandemic. The second stage of the research was carried out with the children of the class, during the period of resumption of face-to-face teaching, in which a playful activity was proposed for the children, in order to assess their socio-emotional state, at the time when they were performing school tasks in the classroom. pandemic. To provide a theoretical basis, we use authors who collaborate in the fields of literacy and who help us understand concepts in education, such as: Corsino (2007), Libâneo (2006), Magda Soares (2004), Klein (2003), Vygotsky (1988) ), Pitombeira and Oliveira (2022), Freire (2011). The results of this investigation indicate that the greatest challenges were concentrated on parents, who did not have electronic resources, in addition to content and tasks that were not very accessible to them. In the same way, the teachers, in addition to not knowing how to deal with electronic resources, were not able to follow the children's development, given that the tasks were not always done by them. It was perceived that the children's main frustrations were missing school and not having the incentive to do homework.